Aid allocation, selectivity, and the quality of governance - Mohammad In'airat (Journal of Economics, Finance and Administrative Science, 2014)
The introduction of good governance in the economic growth and development agenda in the last two decades, along with the failure of aid conditionality to produce positive growth results, motivated ex-post selectivity instead of the ex-ante conditionality as a new approach to aid allocation. This paper aims to explore whether aid selectivity on the basis of the quality of governance is employed as a criterion in foreign aid allocation. The paper uses different instrumental variables as estimators to analyze the determinants of aid allocation over the period 2001–2010. The results produced strong evidence that countries with good governance are given preferential treatment by donors. Among the six governance indicators, it seems that voice and accountability and control of corruption are critical in the aid allocation decision. – – La introducción del buen gobierno en la agenda del crecimiento y el desarrollo económicos durante los dos últimos decenios, junto con el fracaso de la condicionalidad de la ayuda para producir resultados positivos sobre el crecimiento, han motivado la selectividad ex-post en lugar de la condicionalidad ex-ante como nuevo enfoque hacia la asignación de ayuda. Este documento trata de explorar si se utiliza o no la selectividad de la ayuda sobre la base de la calidad del gobierno, como criterio de cara a la asignación de la ayuda. El informe utiliza diferentes estimadores de las variables instrumentales para analizar los determinantes de la asignación de ayuda durante el período 2001-2010. Los resultados arrojaron sólidas pruebas acerca de que los donantes otorgan un tratamiento preferente a los países con buen gobierno. Entre los seis indicadores del buen gobierno, parece que la voz y la responsabilidad, así como el control de la corrupción, son críticos para decidir la asignación de la ayuda.
Keywords: A00; 330; Foreign aid; Aid allocation; Governance; Aid selectivity; Ayuda extranjera; Asignación de ayuda; Gobierno; Selectividad de la ayuda